Height and well-being amongst older Europeans - Kevin Denny (University College Dublin, UCD School of Economics, 2010)
This paper uses a cross-country representative sample of Europeans over the age of 50 to analyse whether individuals' height is associated with higher or lower levels of well-being. Two outcomes are used: a measure of depression symptoms reported by individuals and a categorical measure of life satisfaction. It is shown that there is a concave relationship between height and symptoms of depression. These results are sensitive to the inclusion of several sets of controls reflecting demographics, human capital and health status. While parsimonious models suggest that height is protective against depression, the addition of controls, particularly related to health, suggests the reverse effect: tall people are predicted to have slightly more symptoms of depression. Height has no significant association with life satisfaction in models with controls for health and human capital.
hdl:10197/2670
Keywords: 330; Height; Depression; Well-being; Life satisfaction; Health